Chain-growth polyglycosylation: synthesis of linker-equipped mannosyl oligomers. (11th February 2015) - Schuster, Heiko J.; Vijayakrishnan, Balakumar; Davis, Benjamin G.
Graphical abstract: Highlights: Use of normally erratic intermediates in chain growth polymerization. Enables chain growth 'polyglycosylation'. Allows direct access to functionalized oligosaccharides for use in conjugation. Abstract: Direct syntheses of acetylated poly-mannosides can be achieved in one-step starting from a fully acetylated thioglycoside mannosyl donor using a polymerization-type strategy under the correct conditions. Under conditions that allow polymer growth from non-reducing to reducing end (N→R), different acceptor alcohols can be used as the 'terminating acceptors' to install different linkers at the reducing terminus. The efficiency is dependent on substituents of the linker, its length, temperature and choice of Lewis acid activator.